Embedding operational research into national disease control programme: lessons from 10 years of experience in Indonesia - Mahendradhata, Yodi; Probandari, Ari; Widjanarko, Bagoes; Riono, Pandu; Mustikawati, Dyah; Tiemersma, Edine W.; Alisjahbana, Bachti; Group (TORG), on behalf of the Tuberculosis Operational Research (Global health action, 2014)
There is growing recognition that operational research (OR) should be embedded into national disease control programmes. However, much of the current OR capacity building schemes are still predominantly driven by international agencies with limited integration into national disease control programmes. We demonstrated that it is possible to achieve a more sustainable capacity building effort across the country by establishing an OR group within the national tuberculosis (TB) control programme in Indonesia. Key challenges identified include long-term financial support, limited number of scientific publications, and difficulties in documenting impact on programmatic performance. External evaluation has expressed concerns in regard to utilisation of OR in policy making. Efforts to address this concern have been introduced recently and led to indications of increased utilisation of research evidence in policy making by the national TB control programme. Embedding OR in national disease control programmes is key in establishing an evidence-based disease control programme.
Gesehen am 20.10.2020